Food and Agricultural Organization (FAO) Model Analysis of Training Needs of Artisanal Fishers in Kwara State, Nigeria - Ifabiyi , J. O.; Komolafe, S.E; Adisa , R. S. (Diyala Agricultural Sciences Journal, 2022)
The aim of the study is the Food and Agricultural Organisation (FAO) Model Analysis of Training Needs of Artisanal fishers in Kwara State, Nigeria. Data were collected with the use of a questionnaire and analysed using frequency count, percentages, mean score and Binary Logistic Regression. The food and Agriculture Organisation (FAO) Needs Assessment Model was used to determine the areas of training needs. Any task or skill that had a threshold score above 6.13 requires training intervention. The results revealed that all the respondents were male (100 %), 41.7 years was the average age of the fishers. about 89.3 % of the respondents were married, 45.4% had no formal education, the average years of experience was 26.9 years and 59.7 % of the respondents practiced farming as a supportive occupation. 19.2 kg was the mean quantity of fish caught per day and the mean household size was 8 persons. The fisherfolks required capacity building identification and sorting of fish (x ̅=6.26), handling and transportation of captured fish (x ̅=7.46), canoe use and maintenance (x ̅=6.76), use of chorkor smoker (x ̅=6.7), maintaining personal and environmental health hygiene (x ̅=7.29) and local weather forecasting (x ̅= 6.62). The determinants of training needs on Artisanal Fishing practices were years of fishing experience (p<0.05), income (p<0.05), household size (p<0.10), and membership of a fishing association (p<0.01). The highest ranked constraint affecting artisanal fishing practices was the of storage facilities (x ̅=2.62). The recommendations of the study are that there should be provision of training in the identified areas and provision of supports to the artisanal fisherfolks inform of inputs and credit facilities..